PERLINDUNGAN TERHADAP ANAK SEBAGAI KORBAN EKSPLOITASI DAN KEKERASAN SEKSUAL ANAK SECARA ONLINE - Krisnamurti, Hana; Kunyati, Siti Anah (Jurnal Abdimas Bina Bangsa, 2024)
The existence of Law Number 12 of 2022 concerning the Crime of Sexual Violence is an effort to reform the law to overcome various problems related to sexual violence, including online-based sexual exploitation of victims whose status is still in the child category. The Indonesia Child Protection Commission (KPAI) has recorded the number of cases of sexual violence against children in Indonesia during January - February 2023 there were 119 complaints, while in 2020 there were 25 children victims of violence by the authorities during the eviction of Tamansari and in the city of Bandung there were 431 acts of violence. Sexual violence also occurs in urban areas, including in the densely populated Tamansari Village.  This is because   many parents do not understand the existence of the Child Protection Law and the Sexual Violence Crime Law. The PKM method is carried out by conducting socialization and counseling as well as assistance in the formation of existing institutions in the community to prevent and handle the problem of violence against children.  Socialization is carried out by providing knowledge and understanding to the community, especially parents, about the existence of guarantees in laws and regulations, then providing assistance in reporting cases to the nearest police and institutional readiness for handling. The results of service activities can increase knowledge and open insights and deepen public understanding, especially parents, of the importance of protecting Child Sexual Exploitation and Violence Online so as to increase awareness and legal compliance and is expected to minimize the increase in cases of Child Sexual Exploitation and Violence Online. In preventing and handling these problems, it has been agreed that the institution "Posyandu Remaja or abbreviated Porem" in RW 6 Tamansari Village as a pilot to be given the task of handling children's problems. The agreement was determined because of the existence of the institution so far in dealing with various problems of children and adolescents